Exploring Sociological Perspectives on Visual Art: The Production and Reception of Artworks Created by Blind Artists - Putra, Ida Bagus Komang Sindu; Ghozali, Amir (International Journal of Social Studies, 2026)
This study examines visual artworks created by blind and low-vision artists through a sociology of art lens, focusing on two domains. The first concerns how artworks are produced through material strategies and community-based support networks. The second addresses how artworks are received and interpreted by the public, including reception biases that foreground disability as the primary narrative. Using a descriptive qualitative approach, the study draws on semi-structured interviews that were audio-recorded and transcribed, complemented by artifact analysis of documented artworks. The data were analyzed through thematic coding to map patterns of creative adaptation, forms of accompaniment and support, and mechanisms of legitimization through publication and exhibitions. The findings indicate that artistic production integrates residual visual-form memory in a low-vision artist who experienced vision loss during adolescence, tactile control, and material engineering such as the use of textures and clay to construct relief and enhance form readability. In terms of reception, the public frequently frames blind painting practice as “extraordinary” due to the assumption that visual art must rely primarily on sight, causing appreciation to shift toward emotional admiration. The study argues for a fair evaluative framework and curatorial mediation that re-centres interpretation on artistic decisions and production strategies, so that inclusive art moves beyond normative discourse toward evidence-based practice.